A PRELIMINARY REPORT ON THE GEOLOGY OF THE CENTRAL PART OF THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - イシズカ, ヒデオ; コジマ, ヒデヤス; ISHIZUKA, Hideo; KOJIMA, Hideyasu (National Institute of Polar Research, 1987)
P(論文) The summar party of the 27th Japanese Antarctic Research Expedition (JARE-27) (1985-1986) performed the geological survey in the central part of the Sør Rondane Mountains, East Antarctica. The area is underlain by various kinds of metamorphic and plutonic rocks, of which the metamorphic rocks are tentatively divided by lithology and geologic structure into the northern and southern groups. The northern group is composed mainly of pelitic to psammitic gneisses, while in the southern group basic to intermediate gneisses occur predominantly. Amphibolite and calc-silicate rock also occur as thin layers throughout the area. The metamorphic foliation strikes NE-SW to E-W in the northern group, and N-S to NW-SE in the southern group. There are several synforms and antiforms inferred in the area, of which the axes strike E-W in the northern group and NW-SE in the southern group. This gives rise to the variations of the direction and angle of the dips of the metamorphic foliation. Between the northern and southern groups, a pronounced shear zone of less than 1km wide, characterized by occurrences of cataclastic or mylonitic gneisses, runs from west to east. The mineral assemblages indicate that the majority of the metamorphic rocks may belong to the amphibolite facies, but some portions reach up to the granulite facies. Among the plutonic rocks, granite and granitic pegmatite are predominant, forming large masses or dike swarms, and other rocks such as diorite, dolerite, lamprophyre and ultramafic rock occur as small masses or dikes or lenses. These lithological and structural features of the surveyed area are briefly compared with those reported by JARE-26 (1984-1985) who surveyed the western part of the Sør Rondane Mountains. departmental bulletin paper